Food recommendation system for type 2 diabetes mellitus using content-based filtering / Aisyah Ibrisam and Siti Fatimah Mohd Rum - Ibrisam, Aisyah; Mohd Rum, Siti Fatimah (College of Computing, Informatics, and Mathematics, 2024)
Type 2 Diabetes Mellitus (T2DM) is a significant global health concern, impacting a substantial portion of the population. With T2DM cases on the rise, patients often experience prolonged waiting times for consultations, leading to delayed access to healthcare professionals. Manual food evaluations for T2DM patients, typically reliant on handwritten notes, face challenges due to the lack of suitable datasets and the vast array of food choices. This research introduces a Food Recommendation System for T2DM patients using Content-Based Filtering, with the aim of addressing these issues. Drawing on validated data from certified dietitians, the system focuses on critical attributes such as food category, type, and groups, offering personalized recommendations based on patient preferences. Targeting T2DM patients in Malaysia, the system utilizes data from the Ministry of Health and other reputable sources. The significance of this system lies in its ability to empower T2DM patients to make informed, healthier food choices, thereby contributing to self- management and overall health improvement. In conclusion, this system holds promise for promoting healthier lifestyles among T2DM patients through dietary intervention.